A Reproducible and Scalable Process for Manufacturing a Pfs48/45 Based Plasmodium falciparum Transmission-Blocking Vaccine - Singh, Susheel K.; Plieskatt, Jordan; Chourasia, Bishwanath K.; Fabra-García, Amanda; Garcia-Senosiain, Asier; Singh, Vandana; Bengtsson, Karin Lövgren; Reimer, Jenny M.; Sauerwein, Robert; Jore, Matthijs M.; Theisen, Michael (Frontiers in Immunology, 2021)
The cysteine-rich Pfs48/45 protein, a Plasmodium falciparum sexual stage surface protein, has been advancing as a candidate antigen for a transmission-blocking vaccine (TBV) for malaria. However, Pfs48/45 contains multiple disulfide bonds, that are critical for proper folding and induction of transmission-blocking (TB) antibodies. We have previously shown that R0.6C, a fusion of the 6C domain of Pfs48/45 and a fragment of PfGLURP (R0), expressed in Lactococcus lactis, was properly folded and induced transmission-blocking antibodies. Here we describe the process development and technology transfer of a scalable and reproducible process suitable for R0.6C manufacturing under current Good Manufacturing Practices (cGMP). This process resulted in a final purified yield of 25 mg/L, sufficient for clinical evaluation. A panel of analytical assays for release and stability assessment of R0.6C were developed including HPLC, SDS-PAGE, and immunoblotting with the conformation-dependent TB mAb45.1. Intact mass analysis of R0.6C confirmed the identity of the product including the three disulfide bonds and the absence of post-translational modifications. Multi-Angle Light Scattering (MALS) coupled to size exclusion chromatography (SEC-MALS), further confirmed that R0.6C was monomeric (~70 kDa) in solution. Lastly, preclinical studies demonstrated that the R0.6C Drug Product (adsorbed to Alhydrogel®) elicited functional antibodies in small rodents and that adding Matrix-M adjuvant further increased the functional response. Here, building upon our past work, we filled the gap between laboratory and manufacturing to ready R0.6C for production under cGMP and eventual clinical evaluation as a malaria TB vaccine